Power exhaust and core-divertor compatibility of the baffled snowflake divertor in TCV. (1st March 2023) - Gorno, S; Colandrea, C; Février, O; Reimerdes, H; Theiler, C; Duval, B P; Lunt, T; Raj, H; Sheikh, U A; Simons, L; Thornton, A; Team, The TCV; et al.
Abstract: A baffled snowflake minus low-field side (SF-LFS) is geometrically-optimised in tokamak à configuration variable, increasing divertor neutral pressure, to evaluate the roles of divertor closure (comparing with an unbaffled SF-LFS) and magnetic geometry (comparing with a baffled single null (SN)) in power exhaust and core-divertor compatibility. Ohmically-heated L-mode discharges in deuterium, with a line-averaged core density of approximately 4.7 × 10 19  m −3, are seeded with nitrogen to approach detached conditions. Baffles in the SF-LFS configuration are found to reduce the peak outer target heat flux by up to 23 %, without significantly affecting the location of the inter-null radiation region or the core-divertor compatibility. When compared to the baffled SN, the baffled SF-LFS exhibits a reduction in the outer target heat flux by up to 66 % and the ability to balance the strike-point distribution of heat flux. These benefits are less significant with N2 seeding, with similar peak target quantities (such as heat flux, electron temperature and ion flux) and divertor radiated power. Despite a radiating region located farther from the confined plasma for the SF-LFS than the baffled SN, no change in core confinement is observed. Core effective charge even indicates an increase in core impurity penetration for the SF-LFS. These experiments constitute a good reference for detailed model validations and extrapolations, exploring important physics such as core impurity shielding and the dependence of divertor cross-field transport on magnetic geometry.